Japan’s Cuisine: A Story of Continuity - Leibenstein , Margaret L (Petits Propos Culinaires, 2024)
The author, a member of the Culinary Historians of Boston, recently spent a year in Japan while her husband was a visiting research professor at Kyoto University.